Community‐based Flu Outreach Clinics in South Los Angeles: Client Satisfaction and Experiences. Issue 3 (9th February 2017) - Mobasher, Zahra; Smith, Lisa V.; Stegall, Ashley; Bressler‐Montgomery, Deanna; Dominguez, Daniela; King, Jan; Frye, Douglas; Piron, Jennifer; Family, Leila; Kuo, Tony
Abstract: Objective: This study sought to better understand and improve influenza vaccination in low‐income populations regardless of their health insurance/immigration status. It assessed client satisfaction and experiences with services provided at community‐based "flu outreach" clinics in South Los Angeles. The clinics represent a community‐public agency partnership—a model of vaccine delivery that was relatively novel to the region. Design and Sample: During 2011–2012, a self‐administered questionnaire was distributed to clients of the local health department's 39 flu outreach clinics in South Los Angeles. Measures: The study utilized a 10‐item satisfaction scale and survey questions that gauged client history and experiences with present and prior vaccinations. Results: Of 4, 497 adults who were eligible, 3, 860 completed the survey (participation rate = 86%). More than 90% were satisfied with their experiences at the clinics. Younger adults were significantly more likely than adults aged 65+ to report not having been vaccinated in the previous year ( p  < .05). No statistical differences were observed by gender or race/ethnicity. Conclusions: High satisfaction with flu outreach services in South Los Angeles suggests that this model for vaccine delivery could lead to meaningful client experience of care. Local health departments could capitalize on this model to improve preventive services delivery for the underserved.